Ketamine Inhibits Ovarian Cancer Cell Growth by Regulating the lncRNA-PVT1/EZH2/p57 Axis - Li, Tao; Yang, Jie; Yang, Ben; Zhao, Guoqing; Lin, Hai; Liu, Qi; Wang, Leiming; Wan, Yingchun; Jiang, Hongyang (Frontiers in Genetics, 2021)
Ketamine is widely used for cancer pain treatment in clinic, and has been shown to inhibit various tumor cells growth. However, the effect of ketamine on ovarian cancer cells growth and the downstream molecules has not been defined. In the present study, we found that ketamine significantly inhibited the proliferation and survival of six ovarian cancer cell lines. Moreover, ketamine induced ovarian cancer cell cycle arrest, apoptosis, and inhibited colony formation capacity. Since lncRNAs have been identified as key regulators of cancer development, we performed bioinformatics analysis of a GEO dataset and found fourteen significantly altered lncRNAs in ovarian cancer patients. We then investigated the effect of ketamine on these lncRNAs, and found that ketamine regulated the expression of lncRNA PVT1. Mechanistically, ketamine regulated P300-mediated H3K27 acetylation activation in the promoter of PVT1. Our RNA immunoprecipitation experiment indicated that PVT1 bound histone methyltransferase enhancer of zeste homolog 2 (EZH2), and regulated the expression of target gene, including p57, and consequently altered ovarian cancer cell biology. Our study revealed that ketamine could be a potential therapeutic strategy for ovarian cancer patients.